Reducing Cholesterol Intake: Are the recommendations valid? - Chan, Joanna K. (1991)
The authors question dietary recommendations for the general public calling for reduced cholesterol intake. Metabolic studies have shown that dietary cholesterol normally induces only small increases in blood cholesterol level. There is evidence that only a portion of the population responds to a change in cholesterol intake; hence lowering dietary cholesterol will be effective for only some.